Activation of Sirtuin-1 by Pinocembrin Treatment Contributes to Reduced Early Brain Injury after Subarachnoid Hemorrhage. (16th November 2022) - Zeng, Yile; Fang, Zhongning; Lai, Jinqing; Wu, Zhe; Lin, Weibin; Yao, Hao; Hu, Weipeng; Chen, Junyan; Guo, Xieli; Chen, Xiangrong
Abstract : Subarachnoid hemorrhage (SAH) as a devastating neurological disorder is closely related to heightened oxidative insults and neuroinflammatory injury. Pinocembrin, a bioflavonoid, exhibits different biological functions, such as immunomodulatory, anti-inflammatory, antioxidative, and cerebroprotective activities. Herein, we examined the protective effects and molecular mechanisms of pinocembrin in a murine model of SAH. Using an endovascular perforation model in rats, pinocembrin significantly mitigated SAH-induced neuronal tissue damage, including inflammatory injury and free-radical insults. Meanwhile, pinocembrin improved behavior function and reduced neuronal apoptosis. We also revealed that sirtuin-1 (SIRT1) activation was significantly enhanced by pinocembrin. In addition, pinocembrin treatment evidently enhanced peroxisome proliferator-activated receptor- γ coactivator expression and suppressed ac-nuclear factor-kappa B levels. In contrast, EX-527, a selective SIRT1 inhibitor, blunted the protective effects of pinocembrin against SAH by suppressing SIRT1-mediated signaling. These results suggested that the cerebroprotective actions of pinocembrin after SAH were through SIRT1-dependent pathway, suggesting the potential application of pinocembrin for the treatment of SAH.